2019
DOI: 10.18502/ijps.v14i2.990
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Neurocognitive Profile of Patients with Borderline Personality and Bipolar–II Disorders

Abstract: Objective: The present study was conducted to compare neurocognitive profile in patients with borderline personality disorder (BPD) and bipolar II disorder (BD-II) and to find whether BPD can be classified as one of bipolar spectrum disorders. Method: A total of 35 patients with BPD and 35 euthymic patients with BDII disorder were selected by convenience sampling method. These 2 groups were compared with 30 healthy individuals using neurocognitive battery tests that assessed cognitive flexibility and set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This is in line with earlier reports of lower prefrontal cortex glucose metabolism [ 12 ] and lower connectivity between the prefrontal cortex and amygdala [ 13 ] in BPD compared to BD. The lower prefrontal cortex activity in patients with BPD may be linked to poorer response inhibition, planning [ 50 ], decision-making [ 51 ] and psychosocial functioning [ 52 ] in these patients compared to those with BD. Furthermore, frontotemporal oxy-haemoglobin changes measured with the fNIRS protocol used in this study has been previously shown to distinguish patients with major depression from both HCs and patients with BD or schizophrenia [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with earlier reports of lower prefrontal cortex glucose metabolism [ 12 ] and lower connectivity between the prefrontal cortex and amygdala [ 13 ] in BPD compared to BD. The lower prefrontal cortex activity in patients with BPD may be linked to poorer response inhibition, planning [ 50 ], decision-making [ 51 ] and psychosocial functioning [ 52 ] in these patients compared to those with BD. Furthermore, frontotemporal oxy-haemoglobin changes measured with the fNIRS protocol used in this study has been previously shown to distinguish patients with major depression from both HCs and patients with BD or schizophrenia [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quality assessment for included studies is presented in Supplementary Table S1 . Overall summary scores ranged from 0.55 [ 52 , 56 ] to 0.95 [ 3 , 37 ]. Thirty-three percent of studies scored between 0.85 and 1.0, 56% between 0.70 and 0.84, and 10% between 0.55 and 0.69.…”
Section: Resultsmentioning
confidence: 99%
“…Akbari et al ( 40 ) found that euthymic patients with BD-II and BPD had a poorer performance than HC in most neurocognitive domains, specifically in cognitive flexibility and set-shifting, decision-making, sustained and selective attention and problem-solving. In addition, BPD patients had more elevated response inhibition deficits than BD-II patients, which may contribute to greater impulsivity and poor affect regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Discrepancies were resolved by two independent researchers, IG and AVG. 147 full-text articles were assessed for eligibility and a total of 28 studies published since 1980 met the inclusion and exclusion criteria: 19 focused on assessing clinical features (19,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), six evaluated neuropsychological functioning (40)(41)(42)(43)(44)(45) and three assessed similarities and differences in neuroimaging aspects (46)(47)(48). The study selection process can be seen in Figure 1.…”
Section: Eligibility Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation